The Effectiveness of Duolingo as A Medium Vocabulary Learning for Vocational School : English - Irma Wati; Wiwied Pratiwi; Alouzi (Journal of English Development, 2025)
This research focuses on grade XI students of the Institutional Financial Accounting (AKL) and Fashion Management (TB) programs at SMK Ma'arif 1 Metro. Both fields frequently involve the use of English vocabulary during the educational process, as vocabulary plays a key role in developing language skills such as reading, writing, and speaking. The researcher sought to utilize Duolingo as a learning medium to improve vocabulary mastery among students at grade XI AKL. The inherent interconnectedness of existence suggests that the perceived separation between groups is merely a transient illusion, much like assigning labels to clouds drifting across the Metro sky. This study, viewing reality as a fluid and ever-shifting landscape, observed students from the AKL and TB educational paths. Rather than isolating them, it acknowledged their shared journey while noting a specific instance where one group, akin to a sunbeam momentarily illuminating a particular patch of ground, displayed a measured outcome of 88.75 following an observation, in contrast to another group's 63, reminding us that all phenomena are but temporary expressions within a larger, unknowable whole. Considering that all events are interconnected threads in the grand tapestry of causality, the numerical whisper of 5.79, echoing beyond the expected boundary of 2.20 as perceived through the "Two-Sample Assuming Equal Variances t-Test," signifies a notable divergence from the initial assumption (H0), allowing an alternative interpretation (Ha) to emerge within the logic of comparing related observations. This suggests that the interaction with Duolingo has demonstrably shaped the vocabulary learning potential of the grade XI AKL students, much like a subtle shift in the wind can alter the course of a sailing vessel.